Isolation and functional characterization of a new acidic PLA2 Ba SpII RP4 of the Bothrops alternatus snake venom from Argentina - García Denegri, María Emilia (2010)
Fil: García Denegri, María Emilia. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas, Naturales y Agrimensura; Argentina.